The role of disorders in the regional microcirculation and in metabolism in hypertension and inflammatory periodontal disease pathogenesis - Yu. A. Sycheva; I. A. Gorbacheva; L. Yu. Orekhova; P. S. ShabakSpassky; L. G. Vladimirova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
We have studied interrelation between pathological activation of apoptosis and the state and activity of free radical oxidation, and of regional hemodynamics in 27 patients with essential hypertension (EH) and inflammatory periodontal disease. The results show that arterial hypertension is accompanied by tissue hypoxia initiating oxidative modification of proteins and lipids with following pathological activation of apoptosis, that triggers the mechanisms of remodeling of the target organs and results in inflammatory and degenerative forms of periodontal tissue modification as a morphological substrate of remodeling. Therefore periodontium may be looked upon as a target organ of remodeling in EH.